Study of Gender and Economic Growth in South Kalimantan - Hairina, Melisa; Sopiana, Yunita (PT. Riset Press International, 2023)
This study aims to analyze how gender inequality affects economic growth. The components used are Life Expectancy, Mean Years of Schooling, and Labor Force Participation Rate, while Economic Growth is through the value of Gross Regional Domestic Product. The analysis technique used is panel data regression analysis using a random effect model. The results of this study are first, gender inequality seen from the component of life expectancy partially has a positive and insignificant effect on economic growth in South Kalimantan Province, the mean years of schooling and the labor force participation rate partially have a negative and significant effect on economic growth in South Kalimantan Province in 2011-2021. Second, gender inequality is seen through the components of life expectancy, the mean years of schooling and the participation rate of the workforce simultaneously influencing economic growth in South Kalimantan Province in 2011-2021.